2007
DOI: 10.1080/02732170701290985
|View full text |Cite
|
Sign up to set email alerts
|

Female Tactics and Strategies of Intimate Partner Violence: A Study of Incident Reports

Abstract: Researchers have debated the extent to which females pursue violence against their male partners for purposes of enforcing or resisting control. In an effort to shed light on this important topic, we examined 43 incident reports of women who were court-referred to a batterer intervention program to explore how and why they engaged in intimate partner violence. Our analysis of the reports revealed that the most common tactic of physical violence was pushing and the most common tactic of psychological violence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 57 publications
(54 reference statements)
0
19
1
Order By: Relevance
“…Twelve (52%) studies (Archer & Graham-Kevan, 2003; Barnett, Lee, & Thelen, 1997; Carrado, George, Loxam et al, 1996; Cascardi & Vivian, 1995; Dobash & Dobash, 2004; Hamberger & Guse, 2005; Hamberger, Lohr, & Bonge, 1994; Henning, Jones, & Holdford, 2005; Kernsmith, 2005; O'Leary & Slep, 2006; Rosen, Stith, Few et al, 2005; Sarantakos, 2004) included both men and women, with five enrolling couples (Cascardi & Vivian, 1995; Dobash & Dobash, 2004; O'Leary & Slep, 2006; Rosen, Stith, Few et al, 2005; Sarantakos, 2004). Sixteen (70%) studies recruited women from IPV shelters, prisons, or batterers’ treatment programs (Archer & Graham-Kevan, 2003; Barnett, Lee, & Thelen, 1997; Dobash & Dobash, 2004; Downs, Rindels, & Atkinson, 2007; Flemke & Allen, 2008; Hamberger, Lohr, & Bonge, 1994; Hamberger, 1997; Hamberger & Guse, 2005; Henning, Jones, & Holdford, 2005; Kernsmith, 2005; Miller & Meloy, 2006; Saunders, 1986; Seamans, Rubin, & Stabb, 2007; Stuart, Moore, Hellmuth et al, 2006; Swan & Snow, 2003; Ward & Muldoon, 2007). Nine (39%) studies recruited from a health care-based or community-based sample (Archer & Graham-Kevan, 2003; Carrado, George, Loxam et al, 1996; Cascardi & Vivian, 1995; O'Leary & Slep, 2006; Olson & Lloyd, 2005; Rosen, Stith, Few et al, 2005; Sarantakos, 2004; Swan & Snow, 2003; Weston, Marshall, & Coker, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve (52%) studies (Archer & Graham-Kevan, 2003; Barnett, Lee, & Thelen, 1997; Carrado, George, Loxam et al, 1996; Cascardi & Vivian, 1995; Dobash & Dobash, 2004; Hamberger & Guse, 2005; Hamberger, Lohr, & Bonge, 1994; Henning, Jones, & Holdford, 2005; Kernsmith, 2005; O'Leary & Slep, 2006; Rosen, Stith, Few et al, 2005; Sarantakos, 2004) included both men and women, with five enrolling couples (Cascardi & Vivian, 1995; Dobash & Dobash, 2004; O'Leary & Slep, 2006; Rosen, Stith, Few et al, 2005; Sarantakos, 2004). Sixteen (70%) studies recruited women from IPV shelters, prisons, or batterers’ treatment programs (Archer & Graham-Kevan, 2003; Barnett, Lee, & Thelen, 1997; Dobash & Dobash, 2004; Downs, Rindels, & Atkinson, 2007; Flemke & Allen, 2008; Hamberger, Lohr, & Bonge, 1994; Hamberger, 1997; Hamberger & Guse, 2005; Henning, Jones, & Holdford, 2005; Kernsmith, 2005; Miller & Meloy, 2006; Saunders, 1986; Seamans, Rubin, & Stabb, 2007; Stuart, Moore, Hellmuth et al, 2006; Swan & Snow, 2003; Ward & Muldoon, 2007). Nine (39%) studies recruited from a health care-based or community-based sample (Archer & Graham-Kevan, 2003; Carrado, George, Loxam et al, 1996; Cascardi & Vivian, 1995; O'Leary & Slep, 2006; Olson & Lloyd, 2005; Rosen, Stith, Few et al, 2005; Sarantakos, 2004; Swan & Snow, 2003; Weston, Marshall, & Coker, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…One additional study grouped anger with other motivations, making its unique contribution difficult to disentangle (Archer & Graham-Kevan, 2003). Of 14 studies that ranked or compared motivations based on frequency of endorsement (Barnett, Lee, & Thelen, 1997; Carrado, George, Loxam et al, 1996; Cascardi & Vivian, 1995; Hamberger, 1997; Hamberger & Guse, 2005; Henning, Jones, & Holdford, 2005; Kernsmith, 2005; O'Leary & Slep, 2006; Olson & Lloyd, 2005; Saunders, 1986; Seamans, Rubin, & Stabb, 2007; Stuart, Moore, Hellmuth et al, 2006; Swan & Snow, 2003; Ward & Muldoon, 2007), two found that anger/emotion release was the most common reason (39%) that women reported using IPV (Barnett, Lee, & Thelen, 1997; Stuart, Moore, Hellmuth et al, 2006), and one found that anger/coercion (50–52%) was the top-ranking motivation (Cascardi & Vivian, 1995). Olson & Lloyd (2005) documented that “psychological factors,” which grouped anger with other emotions, were the most common motivation for IPV.…”
Section: Resultsmentioning
confidence: 99%
“…If women defend themselves from men's violence, the violence may escalate further (Fojtik, 1977(Fojtik, -1978Ward & Muldoon, 2007). Bachman and Carmody (1994) found that fighting back against intimate partners is more likely to lead to injuries for women than fighting back against strangers.…”
Section: Reason 8: Men May Physically Retaliate Against Womenmentioning
confidence: 99%
“…In his examination of the reasons given by 52 women arrested for acts of intimate partner violence, Hamberger (1997) found that the most commonly given reason was self-defense (N = 24), followed by "expressing feelings/tension (N = 10). Finally, Ward and Muldoon (2007) examined incident reports for 43 women referred to batterer treatment programs in South Carolina and found that in 33% of the incidents self-defense was a reason for employing violence.…”
Section: Studies That Focus Solely On Female Offendersmentioning
confidence: 99%